Thermalism in Portugal: corporate response to the COVID-19 pandemic – Strategy, Safety, Human Resources and marketing approach: - Oliveira, Ivo (2022)
Framework: Health tourism is currently one of the fastest growing forms of tourism. In Portugal, the “Tourism Strategy 2027” highlighted thermal activity as a means of economic development in the country's regions. On March 11, 2020, WHO declared a covid-19 pandemic. In Portugal, all thermal establishments took the initiative to suspend activity. After the lockdown period the units had to adapt to restart following the guidelines of the health authorities. Goals This study aims to emphasize the spa health tourism sector in Portugal in the context of the Covid-19 pandemic, analyze consumer behavior, and suggest future research on the topic. Paper organization: We present qualitative research, through content analysis using WebQDA software and a bibliometric analysis of co-occurrence of keywords in the thermal field, using the VOSviewer software. The analysis was conducted considering public statements from representatives of 21 units in mainland Portugal, published in the media, as of March 2020. Results: The analyses point to a high appreciated value by the customers to the item safety and to the aesthetic and medicinal treatments. There were no differences in behavior between public and private entities. All regions in mainland Portugal behaved the same way in terms of compliance with the health organization's guidelines, seeking to give the customer more safety and confidence. The training and actions of the human resources were essential to adapt the spas to guarantee strict safety and hygiene rules, as well as the respect for physical distance. In terms of marketing and innovation, the biggest references from the clients are at the product level. Final considerations: The current context of the Covid-19 pandemic favors the use of spas for their curative aspect related to lung problems, post-disease. There are several opportunities for hydrotherapy and research associated with the sector. It is important to draw new lines connected to its potential role in accelerating healing and prevention of coronavirus.